The Role Of Forensic Audit In Disclosing Cases Of Gratification Muhammad Tamzil - Ismail; Fadhlan Fachri; Meilisa Fajarwati; Sahnidar; Fildzah Shabrina; Topan Lilian Napitupulu; Rahima Br. Purba (International Journal of Management, Economic and Accounting, 2025)
This article aims to analyze the gratification case involving the Regent of Kudus, Muhammad Tamzil, and to highlight the important role of forensic audit in uncovering and proving the corruption that occurred. Through this case study, the modus operandi of gratification in the context of local government will be explored, the challenges faced in the process of proof, and how investigative techniques in forensic audit can be an effective tool for law enforcement and corruption prevention efforts. In addition, this article will also discuss the implications of this case for good governance, as well as the importance of strengthening the internal control system.